2018
DOI: 10.1089/jir.2017.0060
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Cellular Immune Response to Recombinant Fragments of Filamentous Hemagglutinin and Pertactin ofBordetella pertussisin BALB/c Mice

Abstract: Vaccination with whole-cell or acellular (Ac) vaccines has been very effective for the control of pertussis. The immune response to Ac vaccines has been generally associated with a shift toward the Th2 profile. In the present study, overlapping recombinant fragments of filamentous hemagglutinin (FHA) and pertactin (PRN) were produced in Escherichia coli. BALB/c mice were immunized with recombinant FHA and PRN together with the native pertussis toxin and alum or CpG as adjuvant. Immunized mice were subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Synthetic CpG oligodeoxynucleotides (ODNs) that mimic this process have adjuvant capacity, generate strong Th1 responses in mice and humans and are capable of overriding the alum-driven Th2 bias when used in combination with alum [ 188 , 189 , 190 ]. The addition of CpG ODNs to an aP vaccine, either with or without alum, increased anti-PT IgG2a serum antibody titers [ 191 ] and robustly induce IFN-γ-producing splenic T cells [ 192 ]. Ross et al showed that an experimental aP vaccine formulated with CpG alone induced B. pertussis -specific Th1 and Th17 responses, and IgG2 antibody responses in mice [ 16 ].…”
Section: Experimental Vaccinesmentioning
confidence: 99%
“…Synthetic CpG oligodeoxynucleotides (ODNs) that mimic this process have adjuvant capacity, generate strong Th1 responses in mice and humans and are capable of overriding the alum-driven Th2 bias when used in combination with alum [ 188 , 189 , 190 ]. The addition of CpG ODNs to an aP vaccine, either with or without alum, increased anti-PT IgG2a serum antibody titers [ 191 ] and robustly induce IFN-γ-producing splenic T cells [ 192 ]. Ross et al showed that an experimental aP vaccine formulated with CpG alone induced B. pertussis -specific Th1 and Th17 responses, and IgG2 antibody responses in mice [ 16 ].…”
Section: Experimental Vaccinesmentioning
confidence: 99%
“…First, tumor cells must express antigens for T cell recognition and activation (immunogenicity). Then, cancer cells should recruit adjuvant-like danger signals such as damage-associated molecular patterns (DAMPs) or pathogen-associated molecular patterns (PAMPs) to boost the immunogenicity (adjuvanticity) ( 63 , 64 ). Conventional chemotherapies improve the immunogenicity and adjuvanticity of cancer cells by inducing cellular death and stress ( Figure 3 ) ( 65 ).…”
Section: Immunomodulatory Effects Of Chemotherapymentioning
confidence: 99%
“…Viral, bacterial, and yeast vectors can also be loaded with genes encoding neoantigens and induce robust immune responses against the tumor (44). These vectors release pathogen-associated molecular patterns (PAMPs) that stimulate the innate and adaptive immune response and increase the infiltration of immune cells into the tumor site (206)(207)(208)(209)(210). Adenoviruses, lentiviruses, retroviruses, and Poxviruses are important viral vectors in vaccine design (211).…”
Section: Cancer Vaccinesmentioning
confidence: 99%